Treatment with Digoxin - is it a clinical challenge? A Retrospective Analysis of Hospitalizations due to Digoxin intoxication - Marcin Wais; Marlena Zając; Dariusz Gruca; Paweł Zalewski; Wiktor Wróblewski; Adam Raabe; Michał Tchórz (Kazimierz Wielki University, 2024)
Introduction and purpose: Digoxin, a cardiac glycoside derived from Digitalis lanata, has stood as a cornerstone in the treatment of various cardiovascular disorders for centuries. This study aims to delve into the demographic aspects, clinical characteristics, and outcomes associated with Digoxin poisoning. By drawing upon a dataset involving 22 patients hospitalized for Digoxin intoxication at the Clinical Department of Toxicology and Cardiology in Lublin, Poland, spanning from April 2014 to December 2023, our investigation seeks to provide an understanding of this issue. Brief description of the state of knowledge: Despite the efficacy of Digoxin, the potential risk of intoxication, especially in the elderly, necessitate a comprehensive examination. Age-related changes, such as declining renal function,  electrolyte imbalances, comorbidities and polypharmacy affect how drugs like Digoxin work. The symptoms of Digoxin poisoning can manifest in various organ systems such as cardiovascular, gastrointestinal, nervous system, highlighting the importance of prompt recognition to seek medical attention. Methods and results: In our study, we analyzed data from 22 patients hospitalized due to Digoxin intoxication, focusing on demographic aspects, clinical characteristics and outcomes. The cases of Digoxin poisoning were categorized according to several factors, including the quantity and nature of substances consumed, the cause of intoxication, gender, age brackets, health conditions, peak serum Digoxin levels, length and outcomes of hospitalization. Conclusions: Our study provides insights into the characteristics and outcomes of patients hospitalized due to Digoxin intoxication. The findings underscore the association of Digoxin poisoning, and emphasize the importance of monitoring serum levels to prevent adverse outcomes. As Digoxin continues to be relevant in treating cardiovascular conditions, our study calls for careful management and monitoring.